2017
DOI: 10.3748/wjg.v23.i11.2044
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic hardness: Correlation of surgeon’s palpation, durometer measurement and preoperative magnetic resonance imaging features

Abstract: AIMTo evaluate the correlation between subjective assessments of pancreatic hardness based on the palpation, objective measurements using a durometer, and magnetic resonance imaging (MRI) findings for assessing pancreatic hardness.METHODSEighty-three patients undergoing pancreatectomies were enrolled. An experienced surgeon subjectively evaluated the pancreatic hardness in the surgical field by palpation. The pancreatic hardness was also objectively evaluated using a durometer. Preoperative MRI findings were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 20 publications
0
15
0
Order By: Relevance
“…A durometer measures a material's hardness or resistance to deformation by applying an indentation load on the specimen, giving a measure of tissue hardness based on an arbitrary Shore unit (HA) [30,31]. Durometers have been used in various medical applications, such as in dermatology [32,33] and for measurements of organ [34][35][36], breast [37], and muscle [38] tissue. The intrarater and inter-rater reliability measures of durometer measurements of epidermal tissue were good to excellent [32,33].…”
Section: Resultsmentioning
confidence: 99%
“…A durometer measures a material's hardness or resistance to deformation by applying an indentation load on the specimen, giving a measure of tissue hardness based on an arbitrary Shore unit (HA) [30,31]. Durometers have been used in various medical applications, such as in dermatology [32,33] and for measurements of organ [34][35][36], breast [37], and muscle [38] tissue. The intrarater and inter-rater reliability measures of durometer measurements of epidermal tissue were good to excellent [32,33].…”
Section: Resultsmentioning
confidence: 99%
“…Although some studies have shown the predictive ability of MRI for pancreatic fibrosis, 11,25,26 the association between the pancreatic density on CT and pancreatic hardness or fibrosis has hardly ever been evaluated. Hashimoto et al showed the pancreatic late/early (L/E) attenuation ratio was positively correlated with pancreatic fibrosis and PF in their retrospective study.…”
Section: Discussionmentioning
confidence: 99%
“…Because pancreatic hardness can only be determined intraoperatively, several studies have evaluated novel parameters that can be measured using preoperative computed tomography (CT) or magnetic resonance imaging (MRI) to predict the texture of the pancreas and the risk of development of PF. [11][12][13] Although these parameters may enable us to make preoperative and objective assessments of the risk for PF, they are often troublesome and have not been generally used.…”
Section: Introductionmentioning
confidence: 99%
“…The reason may be that the dilated pancreatic duct is related to pancreatic fibrosis. The fibrosis hardens the pancreas and thickens the pancreatic duct, resulting in a low incidence of fistulas after pancreaticoduodenectomy [ 25 ]. The thin pancreatic duct is not conducive to anastomosis and drainage of pancreatic juice, which increases the risk of POPF.…”
Section: Discussionmentioning
confidence: 99%